New regional records of vascular plants from Kyrgyzstan - Seregin, Alexey P.; Lyskov, Dmitry F.; German, Dmitry A. (Acta Biologica Sibirica, 2025)
We present and discuss noteworthy floristic records obtained during the Moscow University summer expedition to Kyrgyzstan in 2016. Three taxa are reported as new for Kyrgyzstan: a native species (Utricularia australis R. Br.), an established alien (Artemisia verlotiorum Lamotte), and a nothospecies of local origin (Arctium × ambiguum (Čelak.) Nyman). Additionally, we document 31 species (26 native and 5 alien – Anthemis ruthenica M. Bieb., Atriplex oblongifolia Waldst. et Kit., Chenopodium vulvaria L., Lepidotheca suaveolens (Pursh) Nutt., and Medicago sativa L. s. l.) as new records for one of the seven floristic regions defined in the standard national checklist. These include 12 new records for Western Tian Shan, six for the Alay Valley, six for Inner Tian Shan, four for Fergana, three for the Ysyk-Köl Depression, and two for Northern Kyrgyzstan. Furthermore, we provide supplementary records for 12 species previously overlooked in the national checklist, supported by historical references and newly collected specimens.